PLAIDOYER ET LOBBYING : LES TOILES DE SIGNIFICATION DE DEUX STRATEGIES D'INFLUENCE DES POLITIQUES PUBLIQUES - HINNOU, C. M. Patrick; KOUIN, BARNABÉ JAURÈS (My University, 2022)
How are the social uses of advocacy and lobbying expressed as instruments and strategies for influencing public policies within the reach of non-state actors? This scientific article tries to answer this main question by analyzing the social, even political function of these last two concepts. The aim therefore comes down to freeing oneself from their “misleading familiarity” in order to explore and understand in depth their “webs of meaning”. Essentially based on in-depth documentary research and a structuring analysis, this reflection is positioned not as an empirical study, but as a theoretical and fundamental contribution. She nevertheless remains sensitive to interpretative anthropology in its effort to elucidate the “webs of meaning” of advocacy and lobbying, the uses and misuses of which are sometimes embedded in interactions around the implementation of public policies in Benin. Endorsing Weberian comprehensive sociology, the approach does not privilege the emic or etic statutes of advocacy and lobbying in isolation, but rather adopts their complementarity and elucidates their specificities, their analogies, then their dissimilarities in the arena of development in general and that of elections particularly. In addition to putting into perspective the semantic scope integrating the pillars, even the stages of advocacy and lobbying, the research reveals, from a comparative approach, their own theoretical and practical specificities. It also reveals legal confusion, a perception of blurred formal boundaries, convergence in terms of impact on public action and political competition, a possible rapprochement via general interest and particular interest, then a questioning proximity to the issue of time and space.
Keywords: Advocacy; Lobbying; Webs of Meaning; Interests; Public Policies; CSO; Influence strategies.